La persistencia como fortaleza de carácter presente en estudiantes de licenciatura del centro de actualización del magisterio de Durango, México - Muñoz López, Miguel Ángel (2018)
The students of the Bachelor’s Degree in Secondary Education, with Specialization in Civic Education and Ethics, in mixed modality, of the Centro de Actualización del Magisterio, face exclusive difficulties of the modality, such as: economic deficiencies, minimum rest periods, extended duration of the Career, among others; in order to know their Strengths of Character, a research was made on the trait of Perseverance (VIA, 2017) in character, this within the context of Positive Psychology. The instrument used for data collection was the VIA-240 Inventory. The data obtained in the research showed that the students present a high level of Persistence.